Effects of Feed Truck RPM on Pellet Quality, Unloading Speed, and Feed Line Location on Pellet Quality and Nutrient Segregation - J. A. De Jong; J. M. DeRouchey; B. Haberl; H. Williams; M. D. Tokach; R. D. Goodband; J. C. Woodworth; S. S. Dritz; C. R. Stark; C. K. Jones; L. McKinney; D. Van Otterloo (Kansas Agricultural Experiment Station Research Reports, 2015)
Two separate studies were conducted at one commercial feed mill and six commercial wean-to-finish pig sites in northwest Iowa to determine the effects of feed truck unloading auger RPM on pellet quality and unloading time (Exp. 1) and the effects of feed line location on pellet quality and nutrient concentration of intact pellets and their fines (Exp. 2). For Exp. 1, feed samples were taken from each compartment of an 8-compartment, 24-ton Walinga (Walinga Inc., Guelph, Ontario) feed truck. Feed was unloaded using 3 unloading speeds as determined by the truck RPM of 900, 1,150, and 1,400. Each compartment was timed during unloading, and percentage fines and PDI were determined from each sample taken. The same truck was used 6 times, allowing for 16 replications per unloading speed and 6 replications per compartment. The compartment located closest to the truck cab was denoted as compartment 1, and the compartment located closest to the rear of the truck was denoted as compartment 8. An unloading speed × trailer compartment interaction (P = 0.031) was observed. The difference in unloading time for each compartment became progressively less, the closer the compartment was to the back of the truck. The percentage of fines formed was not significantly different among unloading speeds. The percentage of fines formed during unloading tended to increase (quadratic; P = 0.081) from the first to the eighth compartment, with the maximum percentage of fines formed occurring in the fifth compartment. In Exp. 2, pelleted feed was sampled as feed was unloaded into a commercial feed bin at 6 wean-to-finish barn sites. Each barn was equipped with 2 separate feed lines that transported feed from the bin into the barn. Feed samples were taken inside the barn at the feeder closest to the bin (20 ft), halfway from the bin (115 ft), and the farthest from the bin (250 ft) for each feed line. Samples were analyzed for percentage fines and PDI. During analysis, fines and complete pellets were separated, and a nutrient profile was determined for each. No interactions were observed between feed line location and nutrient profile of the fines and pellets. There was no effect of feed line location on pellet PDI, percentage fines, percentage fines formed, or pellet and fines nutrient profile. Fines had decreased (P<0.05) CP and P but increased (P<0.05) ADF, crude fiber, Ca, ether extract, and starch were observed when compared to the composition of pellets. In conclusion, feed flow from the compartments closer to the cab resulted in fewer fines formed from loading to unloading. Decreasing unloading speed significantly increased the amount of time taken to unload a feed truck. No differences were observed in the amount of fines formed for any of the unloading speeds. There appear to be no differences in pellet quality among feed line locations within a commercial wean to finish barn; however, there are significant differences in nutrient profile between fines and pellets.
Keywords: feed line; feed mill; feed truck; fines; pellets; PDI